Optimization of the operation of the compressor diaphragm unit pumping gas and liquid in rocket complexes by means of a pressure jump calculation program - V. I. Kuznetsov; I. O. Shchuka (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The issue of increasing the service life of the membrane in a diaphragm-plunger compressor is considered. It is found that the uniform distribution of holes in the substrate for the supply of oil to one cavity and gas to the other cavity, which are located between the membrane and the substrates, causes a wavelike movement of the membrane. It is shown which process causes the occurrence of pressure surges that shorten the life of the mekmbran6a to destruction. Theoretically and experimentally, the optimal arrangement of holes in the substrates has been found to reduce pressure surges and increase the service life of the membrane without destruction.